Penerapan Manajemen Sarana dan Prasarana Pendidikan di Madrasah untuk Meningkatkan Kualitas Pembelajaran - Amalia, Tiara; Afifah, Andi Rifkah; Prasetyo, Arif (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2025)
This study aims to analyze the management of educational facilities and infrastructure at MAN 1 Aceh Tamiang through the application of management functions, namely planning, organizing, implementing, and monitoring and evaluation. The research method uses a qualitative descriptive approach with data collection through observation, interviews, and documentation. The results of the study indicate that the planning of facilities and infrastructure is carried out in a participatory manner by considering strategic needs and school budgets, although educational technology development planning still needs to be improved. The organization of facilities and infrastructure is carried out with a clear structure and organized division of tasks, involving the principal, vice principal of infrastructure, treasurer, inventory administration staff, and room coordinator. The implementation of this systematic management of facilities and infrastructure has supported the creation of an effective and efficient learning environment, although budget constraints are still a major challenge. This study contributes to the development of an adaptive and participatory model of educational facilities and infrastructure management, as a reference for other schools in optimizing educational facility management in order to improve the quality of the learning process. In addition, the results of this study also serve as a basis for policy makers in formulating more effective and efficient funding and facility management strategies.